2023
DOI: 10.1111/imm.13699
|View full text |Cite
|
Sign up to set email alerts
|

NLRP2 in health and disease

Tongtong Zhang,
Fei Xing,
Mingcui Qu
et al.

Abstract: NLR family pyrin domain containing 2 (NLRP2) is a novel member of the Nod‐like receptor (NLR) family. However, our understanding of NLRP2 has long been ambiguous. NLRP2 may have a role in the innate immune response, but its ‘specific’ functions remain controversial. Although NLRP2 can initiate inflammasome and promote inflammation, it can also downregulate inflammatory signals. Additionally, NLRP2 has been reported to function in the reproductive system and shows high expression in the placenta. However, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 99 publications
(119 reference statements)
0
0
0
Order By: Relevance
“…NLRP2 has diverse functions, including IFN inhibition and inflammation promotion outside of inflammasome activation, varying across cell types. Further biochemical research is required to fully comprehend the activation, assembly, and functional role of NLRP2 [150].…”
Section: Inflammasome In Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…NLRP2 has diverse functions, including IFN inhibition and inflammation promotion outside of inflammasome activation, varying across cell types. Further biochemical research is required to fully comprehend the activation, assembly, and functional role of NLRP2 [150].…”
Section: Inflammasome In Multiple Sclerosismentioning
confidence: 99%
“…NLRP2, while capable of inflammasome formation, may also exhibit anti-inflammatory effects. In 2004, Bruey et al have suggested that NLRP2 functions as a modulator of NF-κB activation in macrophages, emphasizing its significance in regulating inflammatory signals across different cell types [150]. Although AIM2's involvement in MS has been proposed, limited information exists regarding its specific role in this autoimmune condition [154].…”
Section: Inflammasome In Multiple Sclerosismentioning
confidence: 99%